IL-2high tissue-resident T cells in the human liver: Sentinels for hepatotropic infection - Pallett,LJ; Davies,J; Colbeck,EJ; Robertson,F; Hansi,N; Easom,NJW; Burton,AR; Stegmann,KA; Schurich,A; Swadling,L; Gill,US; Male,V; et al. (Journal of Experimental Medicine, 2017)
The liver provides a tolerogenic immune niche exploited by several highly prevalent pathogens as well as by primary and metastatic tumors. We have sampled healthy and hepatitis B virus (HBV)-infected human livers to probe for a subset of T cells specialized to overcome local constraints and mediate immunity. We characterize a population of T-betloEomesloBlimp-1hiHobitlo T cells found within the intrahepatic but not the circulating memory CD8 T cell pool expressing liver-homing/retention markers (CD69+CD103+ CXCR6+CXCR3+). These tissue-resident memory T cells (TRM) are preferentially expanded in patients with partial immune control of HBV infection and can remain in the liver after the resolution of infection, including compartmentalized responses against epitopes within all major HBV proteins. Sequential IL-15 or antigen exposure followed by TGFβ induces liver-adapted TRM, including their signature high expression of exhaustion markers PD-1 and CD39. We suggest that these inhibitory molecules, together with paradoxically robust, rapid, cell-autonomous IL-2 and IFNγ production, equip liver CD8 TRM to survive while exerting local noncytolytic hepatic immunosurveillance.